It is the general form of a quadratic equation.
A quadratic equation.
2x^2 + 8x + 3 = 0
The equation ax2 + bx + c = 0, where a != 0 is called quadratic.
If a = b then it is a circle; otherwise it is an ellipse.
ax2 + bx +c is an expression, not an equation. It cannot, therefore, have a solution. If the question concerns the equation ax2 + bx + c = 0 then the answer is ax2 - 16ax + 64a = 0 for any a other than 0.
Yes that about sums it up.
x^2 + 3x + 7 = 6x + 18 x^2 - 3x - 11 = 0
With the help of the quadratic equation formula
0x2 + 1x - 7 = 0
The answer to this is the Quadratic Formula, which is: (-b +/- (b2 - 4ac)1/2 )/2a -- as you might have guessed, +/- means there are two solutions for this equation.
the value of
ax2+bx+c = 0 is the general form of a quadratic equation which normally has two solutions
Full equation is (-b +/- sqrt(b2 - 4ac))/2a. Try it with x2 - 2x - 3, where a = 1, b = -2 and c = -3...
The first step is to show an example of the quadratic equation in question because the formula given is only the general form of a quadratic equation.
It is a quadratic function which represents a parabola.
A discriminant that is less than zero.
x2-5-4x2+3x = 0 -3x2+3x-5 = 0 or as 3x2-3x+5 = 0
If you mean b^2 -4ac then it is the discriminant of a quadratic equation. If the discriminant equals 0 then the equation has 2 equal roots. If the discriminant is greater than 0 then the equation has 2 different roots. If the discriminant is less than 0 then it has no real roots.
Two: one is 0, the other is -b/a ax2 + bx + c = 0, but c = 0 ⇒ ax2 + bx + 0 = 0 ⇒ ax2 + bx = 0 ⇒ x(ax + b) = 0 ⇒ x = 0 or (ax + b) = 0 ⇒ x = -b/a
For a quadratic equation y=Ax2+Bx+C, the line of symmetry is given by x=-B/2ASo for the equation y=-x2+x+3, B is 1 and A is -1, so the line of symmetry isx=1/2
It gets reflected in the x-axis.